STRATEGIES FOR INCREASING VEGETABLE YIELDS AND PROBLEM SOLUTIONS - Akbarov Muzaffar Shavkatjonvich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Agricultural productivity is crucial for ensuring food security and sustaining a growing global population. Vegetables play a vital role in a balanced diet, providing essential nutrients for human health. However, various challenges such as climate change, pests, diseases, and resource constraints pose significant threats to vegetable production. This abstract explores innovative strategies aimed at enhancing vegetable yield and addresses common problems encountered in agricultural practices.The first section of this abstract discusses climate-smart agricultural practices, including precision farming, sustainable irrigation techniques, and the use of resilient crop varieties. These strategies aim to optimize resource utilization, mitigate the impact of climate change, and enhance overall productivity in vegetable cultivation.